Peranan Guru Dalam Pembelajaran Tematik Integratif Dalam Meningkatkan Pemahaman Dan Hasil Belajar Peserta Didik Kelas Tinggi SD Negeri 091301 Pematang Panei Kabupaten Simalungun Tahun Pelajaran 2022/2023 - Yenny Mariani Napitupulu; Ulung Napitu; Rohdearni Wati Sipayung (Journal on Education, 2023)
Teacher is a professional job. To be able to carry out this task properly, apart from having to meet the requirements of maturity, being physically and mentally healthy, teachers must also have teacher knowledge and skills. In order to be able to convey the knowledge or field of study he teaches, he must master the science or field of study he teaches, the same is the case with teachers who teach in high school classes at the elementary school level. The teacher must have a role in teaching integrative thematic subjects in increasing the understanding and learning outcomes of high school students. This study aims to describe the teacher's role in Integrative Thematic learning, Analyze supporting and inhibiting factors for the teacher's role in Integrative Thematic learning to improve understanding and learning outcomes of high-class students at SD Negeri 091301 Pematang Panei Simalungun Regency and Analyze student learning outcomes after optimizing the teacher's role in Integrative Thematic learning at SD Negeri 091301 Pematang Panei, Simalungun Regency. The approach that the author uses in this study is qualitative, the type of research is descriptive research analysis. The research location was SD Negeru 091301 Pematang Panei District. Collecting data using observation techniques, interviews and documentation. The data analysis technique is by means of data reduction, data presentation, and data verification. Based on the results of research in the field The Role of the Teacher in Integrative Thematic Learning to Improve Understanding and Learning Outcomes of High Grade Students at SD Negeri 091301 Pematang Panei, Simalungun Regency, namely Using a Variety of Learning Methods, Being a Facilitator, Being a Motivator. Supporting and Inhibiting Factors of the Teacher's Role in Integrative Thematic Learning, namely complete teaching materials, available facilities and infrastructure used optimally, learning resources, the role of parents, the teacher himself. Methods Teaching Methods If Not Varied, Curriculum, and the application of discipline. that the analysis of student learning outcomes after optimizing the role of the teacher is getting better in the high class is getting better.